Evaluation of hardness and Surface roughness of 3D printed Acrylic Resin Used for Denture Base - Salah Al-Zubaidi; Basma L. Mahdi; Marwan A. Salman; Mohd Shukor Salleh (Diyala Journal of Engineering Sciences)
The denture base is a critical component of complete or partial dentures, significantly influencing functionality, comfort, and aesthetics. Traditional manufacturing processes for denture bases face challenges such as limited dimensional accuracy, mechanical integrity, and surface quality. To address these limitations, this study aims to evaluate and optimize the effect of digital light processing (DLP) 3D printing parameters on the mechanical properties and surface quality of acrylic resin denture bases. Specifically, the research investigates how layer height and printing orientation influence hardness and surface roughness. Using the L9 orthogonal array of the Taguchi experimental design, nine specimens were fabricated with varying parameter levels (50 mm, 100 mm, and 150 mm for layer height; 0°, 45°, and 90° for printing orientation). Shore hardness (scale D) and surface roughness were measured for each specimen. ANOVA analysis revealed that both parameters significantly impacted the hardness and surface roughness. Maximum hardness (85 HD) and minimum surface roughness (<0.2 µm) were achieved at 50 mm layer height and 0° printing orientation. The study identified comparable contributions of layer height and printing orientation to hardness (51% and 49%, respectively), while layer height exhibited a threefold greater influence on surface roughness (74.25% vs. 25.75%). These findings provide valuable observations for enhancing the parameters of DLP 3D to improve the performance of denture bases.